Negotiating Indonesian and English as Media of Instruction: Students’ Preferences and Identity in Indonesian EFL Classrooms - Khairiah Syahabuddin; Sa’i Sa’i; Nashriyah Nashriyah; Marlin Steffi Marpaung; Neli Zakia (Jurnal Ilmiah Peuradeun, 2026)
Bilingual instruction integrating Indonesian and English has become increasingly prominent in multilingual higher education contexts; however, students’ preferences regarding instructional language use remain underexplored. This study investigated the preferences of Indonesian university students for using Indonesian, English, or both as the medium of instruction in English language classrooms and examined the factors influencing these preferences. Employing a mixed-method sequential explanatory design, data were collected through questionnaires administered to 23 English education students (N = 23), followed by semi-structured interviews with six participants (N = 6). The findings indicated that the students generally preferred bilingual instruction over monolingual approaches. Indonesian was perceived to support comprehension, attention, emotional comfort and classroom participation, while English was associated with academic competitiveness, professional opportunities, and global communication. The study further revealed that students’ preferences were shaped by four interconnected dimensions: self-assurance, identity, glamour, and attentiveness. These findings demonstrated that the students negotiated Indonesian and English as complementary rather than competing linguistic resources within multilingual classroom interaction. The study highlights the importance of more inclusive, learner-centered, and context-sensitive bilingual instructional practices in multilingual higher education settings.